ENDURANCE OF SAFETY LAYER OF CONCRETE BRIDGES’ ELEMENTS - Jacko, F. V. (Science and Transport Progress, 2010)
This paper presents the models and algorithms for determination of longevity of protective coating of reinforced concrete parts of structures by a statistical (Monte-Carlo) method.